2019
DOI: 10.1038/s41598-019-53242-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary short-chain fatty acid intake improves the hepatic metabolic condition via FFAR3

Abstract: Fermented foods represent a significant portion of human diets with several beneficial effects. Foods produced by bacterial fermentation are enriched in short-chain fatty acids (SCFAs), which are functional products of dietary fibers via gut microbial fermentation. In addition to energy sources, SCFAs also act as signaling molecules via G-protein coupled receptors such as FFAR2 and FFAR3. Hence, dietary SCFAs in fermented foods may have a direct influence on metabolic functions. However, the detailed mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 48 publications
1
81
0
4
Order By: Relevance
“…We found that several SCFAs negatively correlated with the expression levels of mRNA involved in hepatic lipid synthesis and degradation. Our results are supported by previous studies in which SCFAs suppressed lipid synthesis in the liver [ 46 ] and the expression levels of FAS and carbohydrate-response element-binding protein (Chrebp) were lower in mice fed SCFAs compared with mice fed cellulose [ 47 ]. Based on these results, we suggest that SCFAs alter the expression of genes related to lipid metabolism in the cecum.…”
Section: Discussionsupporting
confidence: 90%
“…We found that several SCFAs negatively correlated with the expression levels of mRNA involved in hepatic lipid synthesis and degradation. Our results are supported by previous studies in which SCFAs suppressed lipid synthesis in the liver [ 46 ] and the expression levels of FAS and carbohydrate-response element-binding protein (Chrebp) were lower in mice fed SCFAs compared with mice fed cellulose [ 47 ]. Based on these results, we suggest that SCFAs alter the expression of genes related to lipid metabolism in the cecum.…”
Section: Discussionsupporting
confidence: 90%
“…In another study, FFAR3 signalling mediated glucose-stimulated insulin secretion through the Gi/o-sensitive pathway, and FFAR3 signalling negatively mediates insulin secretion [ 64 ]. Moreover, exogenous supplementation of SCFAs can reduce liver fat content and improve liver metabolism by inhibiting the expression of lipid synthesis genes in FFAR3-deficient mice liver but not FFAR2-deficient [ 65 ].…”
Section: G Protein-coupled Receptors (Gpcrs)mentioning
confidence: 99%
“…SCFAs, especially acetate, can significantly reverse ROS production in mesangial cells, and this can be recapitulated by treatment with an agonist for the cognate G protein-coupled receptor (GPCR), free fatty acid receptor 2 (FFAR2) [27]. Furthermore, dietary SCFA (acetate, propionate, and butyrate) intake improves liver metabolism by acting on FFAR3 [28]. Although the literature has indicated that increased levels of propionate promote liver gluconeogenesis in mice [29], results from a clinical study illustrated that propionate supplementation remarkably reduced intrahepatocellular lipid content [30].…”
Section: Discussionmentioning
confidence: 99%